Perceived Social Support dan Academic Buoyancy: Studi Korelasi Pada Mahasiswa Rantau - Tarania Qudri; Fara Ulfa; Reni Susanti; Liliza Agustin (Global Perspectives in Education Journal, 2025)
Students who live away from home are more vulnerable to high levels of stress, which makes it important for them to have good academic buoyancy in order to face academic challenges and succeed in their studies. Perceived social support refers to a person’s perception of social support, which is believed to influence students’ resilience in difficult situations. This study aims to examine whether there is a relationship between perceived social support and academic buoyancy among students who live away from home. Academic buoyancy in these students may increase along with a higher level of perceived social support. This research is a quantitative and correlational study involving 260 students selected through purposive sampling. The instruments used were the Perceived Social Support Scale and the Academic Buoyancy Scale. Data were analyzed using Kendall’s Tau correlation test with the help of the Statistical Package for Social Science (SPSS) version 25 for Windows. The results showed a significant relationship between perceived social support and academic buoyancy. This means that the higher the level of perceived social support, the higher the academic buoyancy of the student. These findings show the importance of consistently receiving support from parents, friends, and significant others to help reduce the burden of academic demands.